Monitoramento de respostas subagudas ao treinamento de força na musculação - Karine Naves de Oliveira Goulart (2015)
The aim of this study was to monitor the sub-acute responses to strength training and correlate them with variation in performance between sessions. The study included 14 trained men that were underwent to a pre-monitoring period for four weeks (sessions 1-7), with the purpose of familiarizing to the training protocol and testing that would be used in experimental situations. After "pre-monitoring", voluntary initiated the experimental conditions over three weeks (sessions 8 to 13) with two sessions per week and randomized intervals of 24, 48 or 72 hours between sessions of each week. The data obtained between the two sessions of each week were compared on a subjective muscle soreness rating, the session rating of perceived exertion (session RPE), the blood concentration of creatine kinase (CK), countermovement jump performance (CMJ), maximum voluntary isometric contraction performance (MVIC) and training session performance, assessed by training total volume. The total volume was not significantly different among the first session (8, 10, 12) of each week monitoring period and the last session of pre-monitoring period (session 7). A significant reduction in the total volume and CK was verified with 24 hours of recovery. The CMJ and MVIC were significantly higher 72 hours after the session. Muscle soreness was significantly higher 24 and 48 hours after training sessions. Significant differences for PSE session were not found. Only the CMJ (r = 0.439, p <0.001), the MVIC (r = 0.389, p <0.001) and muscle pain (r = -0.327, p = 0.005) were significantly correlated with the total volume of training. The familiarization period was crucial to balance the initial response of adaptation and contribute to a similarity between "pre-recovery intervals" sessions of the monitoring period. The variables investigated in this study were not effective to monitor the fatigue caused by the resistance training since its sub-acute changes did not show high correlation values with performance variations.